A Book Review: New Directions, Reading, Writing, and Critical Thinking - Khatri, Dipendra Kumar (Journal of NELTA Surkhet, 2018)
This article presents the review of the book that is prescribed for the Bachelor level course. The purpose of the particular review of the book is to highlight the strengths and weaknesses of the selected book. It is started with the general background of the writer of the book. Then, the objectives, contents are reviewed with other general features. Finally, it was found that maximum contents are selected from the Western World. So, it was concluded to include the texts from the Eastern World and add more pictures to develop critical thinking among the readers.Journal of NELTA Surkhet,  Vol. 5 January, 2018, Page: 113-117